comparison of soil sensitivity to acidification based on laboratory-determined short-term acid buffering capacity and the Skokloster classification - Hodson, M.E; Langan, S.J; Lumsdon, D.G (Water, air, and soil pollution, 1998)
The sensitivity of mineral soils to anthropogenically-induced acidification may be assessed using the Skokloster classification or by considering the short-term acid buffering capacity (STABC). The Skokloster classification is based on the assumption that the majority of acidification neutralization is due to base cation release from mineral weathering. It therefore considers the long-term neutralizing capacity of a soil on a scale of decades. The STABC of a soil is due largely to the adsorption and exchange of H+ ions by soil components, and acts on the scale of single years. The United Kingdom maps generated to identify soils that are sensitive to acidification use the Skokloster classification. A comparison of the laboratory-determined STABC of the different horizons from soil profiles with the Skokloster classes of soils shows that there is generally no correlation between the two. Maps showing soil sensitivity to acidification based on measured STABC and Skokloster classes are markedly different. The STABC measure has the potential for quantitatively assessing a soil's sensitivity to acidification, while the Skokloster approach is empirical. It may be possible to combine the two approaches to produce a dynamic method of assessing soil recovery from acidification.[PUBLICATION ABSTRACT]